1965
DOI: 10.1128/jb.89.4.984-987.1965
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-Absorption Spectra of Dry Bacterial Spores

Abstract: BAILEY, GLEN F. (Western Regional Research Laboratory, Albany, Calif.), SAIMA KARP, AND L. E. SACKS. Ultraviolet-absorption spectra of dry bacterial spores. J. Bacteriol. 89:984-987. 1965.-The possibility of obtaining reasonably satisfactory ultraviolet-absorption spectra of dry spores embedded in KBr has been demonstrated. Such spectra show the three peaks characteristic of calcium dipicolinate. The dipicolinate spectra are more distinct when reference pellets containing appropriate amounts of the analogous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1965
1965
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…Another possibility is that the presence of other constituents such as dipicolinic acid in the vicinity of DNA may affect the spectra by facilitating energy transfer in the unique environment of the spore core. This is supported by the fact that dipicolinic acid exhibits a closely parallel pattern of absorption spectrum in this wavelength region (Bailey et al, 1965). The amount or distribution of this material may be somewhat different in the recombination-defective spores, particularly in RCE spores.…”
Section: Discussionmentioning
confidence: 84%
“…Another possibility is that the presence of other constituents such as dipicolinic acid in the vicinity of DNA may affect the spectra by facilitating energy transfer in the unique environment of the spore core. This is supported by the fact that dipicolinic acid exhibits a closely parallel pattern of absorption spectrum in this wavelength region (Bailey et al, 1965). The amount or distribution of this material may be somewhat different in the recombination-defective spores, particularly in RCE spores.…”
Section: Discussionmentioning
confidence: 84%
“…These results suggest strongly that Ca in the core is bound with DPA if the assumption is accepted that DPA is associated with Ca (4,24,33,34). In other words, it means that DPA is concentrated in the core as the cryptobiotic state of Ca-DPA.…”
Section: Germinated Sporementioning
confidence: 78%
“…The bacterial spore is a microorganism unique in structure and chemical composition as well as in physiological properties. Among the chemical components of the spore, Ca was detected as 1 to 5% of the spore dry weight (6,29), suggesting that it is present mostly in association with dipicolinic acid (DPA) (4,24,33,34), and it has been suggested and thoroughly discussed that Ca plays an important role in spore properties such as high resistance, dormancy, cryptobiosis and germinability (1-3, 7, 8, 19, 21, 22, 26, 27, 32). Considering its role in these mechanisms, the location of Ca is an important factor, and many have suggested that the location of Ca is in the coat, the cortex, or the core (9, 10, 16-21, 25, 28, 30, 31), but there is no definite and direct evidence for these locations.…”
mentioning
confidence: 99%
“…The distribution of DPA and the occurrence of DPA conjugates in the spore have yet to be substantiated, but it is possible that several forms or states of DPA exist in the spore and are located in the cytoplasm or cortex rather than in the spore coat or exosporium (Halvorson and How&, 1961). Bailey et al (1965) have presented ultraviolet absorption spectra of dry bacterial spores that suggest that DPA does exist largely as a calcium chelate in the spore. Windle and Sacks (1963) have found evidence for bonding of copper with protein and for two different types of bonding for manganese in spores, which could lead to speculation on the role of various metallic cations on structure and stability of the spore.…”
Section: And Discussionmentioning
confidence: 99%